2016
DOI: 10.3892/ol.2016.4243
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation effects of elemene on the GSTP1 gene in HCC cell line QGY7703

Abstract: Abstract. The present study aimed to investigate elemene's effects on cell proliferation, apoptosis, and the cell cycle in the hepatocellular carcinoma (HCC) cell line, QYG7703, and to investigate GSTP1 gene methylation change in QGY7703 cells after being treated with elemene to explore whether elemene reversed the abnormal GSTP1 gene methylation. QGY7703 cells were treated with different elemene concentrations. Cell proliferation was measured with MTT assay, cell apoptosis and cell cycle were analyzed by flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…29 Methylation of the GSTP1 gene CpG island promoter is involved in the occurrence and development of multiple tumors, which could be a biomarker for early screen, diagnosis and prognosis. 30 Studies have emphasized the ability of GSTP1 expression is an important predictor of the clinical outcome or drug resistance to ESCC. Lymph node metastasis, and overexpression of GSTP1 were all determined to be independent predictors linked to poor prognoses, with this association tightly correlated with the chemotherapeutic efficacy of 5-FU combined with cisplatin in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 Methylation of the GSTP1 gene CpG island promoter is involved in the occurrence and development of multiple tumors, which could be a biomarker for early screen, diagnosis and prognosis. 30 Studies have emphasized the ability of GSTP1 expression is an important predictor of the clinical outcome or drug resistance to ESCC. Lymph node metastasis, and overexpression of GSTP1 were all determined to be independent predictors linked to poor prognoses, with this association tightly correlated with the chemotherapeutic efficacy of 5-FU combined with cisplatin in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that bELE is a potent anticancer agent against multiple cancers in extensive clinical trials and experimental research in vivo and in vitro. Wu et al found that bELE increased apoptosis and caused S phase arrest of several hepatocellular carcinoma cell lines in a dose‐dependent manner []. In lung cancer, peroxiredoxin‐1, a critical molecule in redox regulation, has been identified and confirmed as a downstream effector suppressed by bELE [].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation associated with SOCS protein silencing has been found in a variety of cancers, including myeloma, melanoma, bladder cancer, liver cancer, gastric cancer, and colorectal cancer. [ 30 ] The effect of risk factors on DNA methylation in HCC needed to be analyzed. Therefore, this study analyzed the effects of sex on the relationship between DNA methylation and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of HCC in men was 4 to 8 times higher than that in women. Wu et al [ 30 ] reported that the methylation of the SOCS3 gene was high in HCC and had no significant correlation with the patient's sex, age, tumor size, and differentiation degree. Li et al [ 31 ] showed that the expression of SOCS3 positively correlated with the prevalence of HCC, but not with the age and sex of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%